"Monocept": A Brief Report of Congenital Absence of the Long Head of the Biceps Tendon and Literature Review. (2nd July 2017) - Winston, Benjamin A.; Robinson, Katlyn; Crawford, Dennis
Abstract : The long head of the biceps tendon plays an important role in shoulder stability and its functional absence has been shown to contribute to glenohumeral instability. Congenital absence of the long head to the biceps tendon is rare, although described in the literature. We report the case of an 18-year-old recreational athlete with recurrent shoulder instability and congenital absence of the long head of the biceps tendon (which we term "monocept") and mild ipsilateral upper extremity hemimelia. The patient was treated surgically with posterior capsular shift with anterior Bankart repair without complication. At 16-month follow-up the patient has returned to recreational activity and has had an 11.37-point improvement in his DASH score. The authors suggest that patients with this uncommon anatomic anomaly and clinical shoulder instability are more likely to require surgical treatment.